Bunuel wrote:

If x^2 + 0.25x - 0.5 = 0, then x(4x + 1) =

A. 0.5

B. 2

C. 3.5

D. 4

E. 0

\(x^2 + 0.25x - 0.5 = 0\)

Multiply by 4: prompt's second expression is a factored version of \(4x^2 + x\). That expression = \((4)(x^2 + 0.25x)\) -- i.e., (4) * the first two terms of the quadratic equation

\((4)x^2 + (4)0.25x - (4)0.5 = 0\)

\(4x^2 + x - 2 = 0\)

\(4x^2 + x = 2\)

\(x(4x + 1) = 2\)

Answer B

_________________

In the depths of winter, I finally learned

that within me there lay an invincible summer.

-- Albert Camus, "Return to Tipasa"